Proteomics and phosphoproteomics study of LCMT1 overexpression and oxidative stress: overexpression of LCMT1 arrests H2O2-induced lose of cells viability. (1st January 2019) - Wang, Xinhang; Tang, Shen; Qin, Fu; Liu, Yuyang; Liang, Ziwei; Cai, Haiqing; Mo, Laiming; Xiao, Deqiang; Guo, Songcao; Ouyang, Yiqiang; Sun, Bin; Lu, Cailing; et al.
ABSTRACT: Objectives: Protein phosphatase 2A (PP2A), a major serine/threonine phosphatase, is also known to be a target of ROS. The methylation of PP2A can be catalyzed by leucine carboxyl methyltransferase-1 (LCMT1), which regulates PP2A activity and substrate specificity. Methods: In the previous study, we have showed that LCMT1-dependent PP2Ac methylation arrests H2 O2 -induced cell oxidative stress damage. To explore the possible protective mechanism, we performed iTRAQ-based comparative quantitative proteomics and phosphoproteomics studies of H2 O2 -treated vector control and LCMT1-overexpressing cells. Results: A total of 4480 non-redundant proteins and 3801 unique phosphopeptides were identified by this means. By comparing the H2 O2 -regulated proteins in LCMT1-overexpressing and vector control cells, we found that these differences were mainly related to protein phosphorylation, gene expression, protein maturation, the cytoskeleton and cell division. Further investigation of LCMT1 overexpression-specific regulated proteins under H2 O2 treatment supported the idea that LCMT1 overexpression induced ageneral dephosphorylation of proteins and indicated increased expression of non-erythrocytic hemoglobin, inactivation of MAPK3 and regulation of proteins related to Rho signal transduction, which were known to be linked to the regulation of the cytoskeleton. Discussion: These data provide proteomics and phosphoproteomics insights into the association of LCMT1-dependent PP2Ac methylation and oxidative stress and indirectly indicate that the methylation of PP2A plays an important role against oxidative stress.